Rola asystenta rodziny w świetle Ustawy o wspieraniu rodziny i systemie pieczy zastępczej – kolejna forma pracy z rodzinami dysfunkcyjnymi - Zieja, Elżbieta (Karkonoska Państwowa Szkoła Wyższa, 2012)
Ustawa o wspieraniu rodziny i systemie pieczy zastępczej (the statute on family support and surrogate care) has obliged municipalities to provide help for dysfunctional families and their children. That is to be brought into effect through the work of the family assistant. The purpose of this help is to make it possible for dysfunctional families to overcome obstacles deriving from the process of the upbringing of young children. The assistant is to help parents fulfill their social functions that might, in effect, lead to the stability of life preventing children from being placed in foster families and institutions.
Keywords: asystent rodziny; rodzina dysfunkcyjna; opieka zastępcza